The ACE I allele is associated with higher endurance efficiency of athletes - Dekany, M.; Harbula, I.; Berkes, I.; Gyoere, I.; Falus, A.; Pucsok, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The ACE I allele is a genetic marker that might be associated with higher endurance efficiency and the adaptation level of the cardiovascular system. In the examination of the genotype besides the measuring of acute physical activity (VO2max, VE/MVVex) it is worth taking into consideration the long-term efficiency (number of medals) of endurance performance also, in the interest of understanding of the more accurate relationship.